Brain-derived neurotrophic factor serum levels in genetically isolated populations: gender-specific association with anxiety disorder subtypes but not with anxiety levels or Val66Met polymorphism. - Carlino, Davide; Francavilla, Ruggiero; Baj, Gabriele; Kulak, Karolina; d'Adamo, Pio; Ulivi, Sheila; Cappellani, Stefania; Gasparini, Paolo; Tongiorgi, Enrico (PeerJ, 2015)
Anxiety disorders (ADs) are disabling chronic disorders with exaggerated behavioral response to threats. This study was aimed at testing the hypothesis that ADs may be associated with reduced neurotrophic activity, particularly of Brain-derived neurotrophic factor (BDNF), and determining possible effects of genetics on serum BDNF concentrations. In 672 adult subjects from six isolated villages in North-Eastern Italy with high inbreeding, we determined serum BDNF levels and identified subjects with different ADs subtypes such as Social and Specific Phobias (PHSOC, PHSP), Generalized Anxiety Disorder (GAD), and Panic Disorder (PAD). Analysis of the population as a whole or individual village showed no significant correlation between serum BDNF levels and Val66Met polymorphism and no association with anxiety levels. Stratification of subjects highlighted a significant decrease in serum BDNF in females with GAD and males with PHSP. This study indicates low heritability and absence of any impact of the Val66Met polymorphism on circulating concentrations of BDNF. Our results show that BDNF is not a general biomarker of anxiety but serum BDNF levels correlate in a gender-specific manner with ADs subtypes.